Nurse-led psychoeducational interventions in patients suffering from schizophrenia or other psychotic disorders and their families: A scoping review protocol. - Carla Gramaglia; Eleonora Gambaro; Lucia Bestagini; Erika Bassi; Alberto Dal Molin; Patrizia Zeppegno (PLoS ONE)
Background Mental health conditions are one of the most significant public health issues. Psychoeducation is an organized, structured, and understanding transfer of knowledge about the disease and its treatment, incorporating inspirational and educational elements to allow patients to achieve better management of their disease and increased treatment adherence and effectiveness, especially for patients with schizophrenia. This review will consider studies that include adults suffering from schizophrenia or other psychotic disorders and their family members. In this scoping review, the rigor expected of all primary and secondary research will be guided by clear and consistent standards governing its design, regardless of the level of inquiry. The review will aims to map the currently available research in nurse-led psychoeducational programs conducted on these populations. Inclusion criteria Adults suffering from schizophrenia or other psychotic disorders and their family members; patients and family members aged from 18 to 75 years old. Both experimental and quasi-experimental study designs, including randomised controlled trials, non-randomised controlled trials, before-and-after studies, interrupted time-series studies, analytical observational studies, and descriptive observational study designs. Intervention: a) psychoeducational interventions on patients suffering from schizophrenia and/or other psychotic disorders and their families, b) nurse-led psychoeducational interventions. Methods and analysis The scoping review will be conducted following the Joanna Briggs Institute methodology for scoping reviews. Medline, Scopus and CINAHL databases will be searched for relevant studies. The reference list of the selected articles will be screened. Data will be summarised in a comprehensive narrative summary to highlight the following for each nurse-led intervention program: main features, setting, and target. Ethics and dissemination This study does not require ethical approval. The study will be submitted to a peer reviewed journal, will be publicly disseminated and will be the topic of research presentations. Review registration number Registered in the Open Science Framework on April 6, 2023. OSF Registration Doi: https://doi.org/10.17605/OSF.IO/ASQ95.